PERKEMBANGAN PENDIDIKAN DAN PERILAKU KEBERAGAMAAN PADA MASA KESULTANAN SAMBAS - Mardiyati, Isyatul (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
From a historical perspective, Sambas Sultanate historically had a significant contribution to the diversity of the empire and the kingdoms in the archipelago. While the educational side of this empire have also contributed to the transmission of the scientific world-Malay archipelago in the context of the development of Islamic education as a chain of intellectual authority (intellectual genealogy) which in turn result in the intensification of the Islamization of Islamic civilization in Indonesia. One role of the educational Sambas Sultanate is their success in producing the best sons of the Malay world and the Islamic world, such as Indra Crown Prince, Ahmad Khatib Sambas and H. M. Basyuni Imran. To find out more about the historical development of science Sambas Sultanate both from within and outside the palace will be presented further in this paper.***Dari perspektif sejarah, Kesultanan Sambas memiliki sumbangan yang signifikan terhadap keragaman kerajaan di kepulauan Indonesia. Sementara itu dari sisi pendidikan kerajaan ini juga memberikan kontribusi bagi transmisi dunia keilmuan di kepulauan Indonesia dalam konteks perkembangan pendidikan Islam sebagai jaringan intelektual (genealogi intelektual) yang pada gilirannya mempengaruhi intensifikasi Islamisasi peradaban Islam di Indonesia. Salah satu peran pendidikan Kesultanan Sambas adalah keberhasilannya dalam menghasilkan putra terbaik dalam dunia Melayu dan Islam, seperti Putra Mahkota Indra, Ahmad Khatib Sambas, dan H.M. Basyuni Imran. Kajian ini akan mengungkap perkembangan sejarah ilmu di Kesultanan Sambas, baik di dalam maupun luar Kesultanan Sambas.